Salvage Therapy Using Azacitidine for Relapsed Primary Myelofibrosis after Cord Blood Transplantation - Sumi, Masahiko; Kitahara, Mari; Shishido, Tsutomu; Kazumoto, Hiroko; Uematsu, Nozomu; Kirihara, Takehiko; Sato, Keijiro; Ueki, Toshimitsu; Hiroshima, Yuki; Kobayashi, Hikaru (Internal Medicine, 2020)
We present the case of a 53-year-old woman with prefibrotic stage primary myelofibrosis (PMF) who underwent cord blood transplantation. Nine years after transplantation, she relapsed, which was confirmed by a bone marrow examination. We decided to treat her using azacitidine. After three courses of azacitidine, a partial cytogenetic response was confirmed. Azacitidine maintenance therapy successfully maintained a low level of recipient-origin peripheral blood cells with a stable hematological condition. Azacitidine may therefore be a promising therapeutic option for PMF patients who relapse after allogeneic stem cell transplantation.